Developing a Circular Economy in China : Highlights and Recommendations - World Bank (Washington, DC, 2014)
China's rapid economic growth over the past decades has been accompanied by substantial depletion of natural resources, degradation of major ecosystems, and serious environmental pollution with adverse impacts on human health. China's government fully recognizes that such trends cannot continue indefinitely and therefore is committed to building a resource-saving and environmentally- friendly society as a stated national policy. It has adopted the circular economy (CE) approach as a core component of its sustainable development strategy. The ultimate objective of the CE approach is to achieve the decoupling of economic growth from natural resource depletion and environmental degradation. The Chinese government has been promoting CE on a number of fronts - legislation, policy reform, pilot projects, and monitoring and evaluation activities. This briefing note highlights and recommends further actions the government should take to enhance the effectiveness of its efforts to develop a circular economy. Based on the findings and results from the World Bank-supported CE studies, the note focuses on four key areas that deserve greater attention: 1) a balanced mix of policy instruments; 2) participation by both industry and the public in the CE approach; 3) capacity building; and 4) the role of the government and governance.